Implementation of a thin, flat water target capable of high-repetition-rate MeV-range proton acceleration in a high-power laser at the CLPU. (1st May 2022) - Puyuelo-Valdes, P; de Luis, D; Hernandez, J; Apiñaniz, J I; Curcio, A; Henares, J L; Huault, M; Pérez-Hernández, J A; Roso, L; Gatti, G; Volpe, L
Abstract: Fluid targets are attractive for laser-driven ion acceleration at high-repetition-rate laser facilities. In particular, liquid targets have several interesting features since they can regenerate in situ and are debris-free (or little) and operate at a high repetition rate. Here, we report high-repetition-rate MeV-range proton acceleration by the interaction of the VEGA-2 laser system with a micrometer-thick water sheet target in a high vacuum (10 −4 mbar) environment. The water target was running continuously at this pressure for 4 h and more than 1000 shots were performed. Two different water thicknesses were studied, and we measured a continuous proton distribution with energies up to 3.5 MeV. Experimental results are compared with the literature and existing scaling laws.